Naturally acquired antibodies against Clostridium perfringens epsilon toxin in goats - Veschi, Josir Laine A.; Bruzzone, Octavio A.; Losada-Eaton, Daniela M.; Dutra, Iveraldo S. [UNESP]; Fernandez-Miyakawa, Mariano E. (Elsevier B.V., 2008)
Clostridium perfringens type D-producing epsilon toxin is a common cause of death in sheep and goats worldwide. Although anti-epsilon toxin serum antibodies have been detected in healthy non-vaccinated sheep, the information regarding naturally acquired antibodies in ruminants is scanty. The objective of the present report was to characterize the development of naturally acquired antibodies against C. perfringens epsilon toxin in goats. The levels of anti-epsilon toxin antibodies in blood serum of goat kids from two different herds were examined continuously for 14 months. Goats were not vaccinated against any clostridial disease and received heterologous colostrums from cows that were not vaccinated against any clostridial disease. During the survey one of these flocks suffered an unexpectedly severe C. perfringens type D enterotoxemia outbreak. The results showed that natural acquired antibodies against C. perfringens epsilon toxin can appear as early as 6 weeks in young goats and increase with the age without evidence of clinical disease. The enterotoxemia outbreak was coincident with a significant increase in the level of anti-epsilon toxin antibodies. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Clostridium perfringens; epsilon toxin; immune response; Caprine